High-quality steel slag aggregate as well as preparation method and application thereof
Through the hierarchical carbonization process, including primary carbonization and reduction, and secondary carbonization treatment, the problems of high free calcium oxide content and long carbonization treatment cycle of steel slag aggregates are solved, and low-density and high-quality steel slag aggregates are quickly prepared. Suitable for the preparation of asphalt concrete.
Patent Information
- Application Number
- CN202411631589.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
In the prior art, the free calcium oxide content of steel slag aggregates is high, resulting in unstable volume, and the conventional carbonization treatment cycle is long and the efficiency is low, making it difficult to meet the application needs of asphalt concrete.
Using the graded carbonization process, firstly the primary carbonization and reduction under high temperature conditions of 1300℃-1500℃, use CO in industrial waste gas to reduce iron trioxide, and then perform secondary carbonization, through spraying and high-pressure carbonization in airtight containers , the free calcium oxide content in the steel slag aggregate is reduced to less than 3%.
It has achieved a significant reduction in the free calcium oxide content in unaged steel slag within 24 hours, and quickly prepared low-density and high-quality steel slag aggregates, which are suitable for the preparation of asphalt concrete.
Smart Images

Figure CN119504156A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid waste resource utilization, and more specifically to a high-quality steel slag aggregate and a preparation method and application thereof. Background Art
[0002] In order to remove various oxides formed by impurities in molten iron during the steelmaking process, slag-forming agents need to be added. Slag-forming agents react with these oxides to form slag. The separated slag is usually discharged from the steelmaking furnace in liquid or semi-liquid form and converted into a solid form after cooling, namely steel slag. As a by-product of the steel industry, steel slag is discharged in China at an annual rate of up to 160 million tons, accounting for about 85% of the global steel slag production, but its comprehensive utilization rate has long been less than 30%. The accumulation of a large amount of steel slag will not only cause a waste of land resources, but also continue to precipitate heavy metal pollution into the soil. Due to its good mechanical properties and low price, steel slag can theoretically provide high-quality cementitious materials and pavement aggregates for the construction industry and the road industry. However, the volume stability of steel slag is poor, and it will expand in a water-rich environment and under the influence of temperature, which restricts its application in road engineering. Gao Ying et al. summarized the existing research in the article "Research Progress on Volume Expansion Behavior and Modification Methods of Steel Slag" and showed that the main reason for the poor volume stability of steel slag is that it contains expansion components such as free calcium oxide, periclase and a high content of metallic iron. When the components are hydrated or oxidized, the volume expansion of the steel slag is inevitable; among them, the high content of free calcium oxide is the key reason.
[0003] At present, the main measure to solve the problem of poor stability of steel slag is to modify the steel slag. The steel slag modification measures include aging modification, reconstruction modification and carbonation modification. Among them, cold slag aging modification is the most commonly used treatment method, but the aging of steel slag needs to be placed outdoors for more than 6 months, and the aging cycle is long and the efficiency is low. The conventional carbonization process mainly grinds the aged steel slag particles into steel slag fine powder or micro powder before carbonizing. Generally, high concentration or pure CO2 is used to carbonize the steel slag powder once, but the carbonization efficiency of steel slag powder at normal temperature and pressure is relatively low. It often takes several days to complete the carbonization of steel slag powder, and the production cycle is long. Compared with steel slag fine powder or micro powder, the conventional carbonization efficiency of steel slag aggregate is lower and the required cycle is longer.
[0004] The existing carbonization treatment of steel slag aggregate is mainly different for different application scenarios of the carbonized steel slag. For example, in patent CN 116874204 A, coarse steel slag with a particle size of 0.075 to 20 mm is first screened from the steel slag, and then the carbon dioxide in the industrial waste gas is wet-captured in a pressurized environment for carbonization treatment, and the powder is ground to prepare cementitious materials; in CN 117534426 A, the steel slag is first mixed with desulfurized gypsum, water and a chelating agent to prepare a slurry, which is then injection molded into a steel slag block blank, and then carbonized using industrial waste gas. However, there is currently no method that can combine the conventional steel slag aggregate preparation process for carbonization treatment to directly prepare high-quality steel slag aggregate for use in asphalt concrete. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a high-quality steel slag aggregate and a preparation method and application thereof, the purpose of which is to combine the conventional steel slag aggregate preparation process for carbonization treatment, and find that high-temperature molten steel slag is used as raw material, and graded carbonization is adopted. First, industrial waste gas is introduced under high temperature conditions of 1300℃-1500℃ for primary carbonization and reduction. While reducing free calcium oxide, the ferric oxide in the steel slag is reduced to elemental iron and ferroferric oxide by CO in the industrial waste gas, and then the particles below 10mm are screened for secondary carbonization to reduce the free calcium oxide content in the steel slag aggregate to less than 3%, and high-quality steel slag aggregate is directly obtained by magnetic separation. This method can reduce the free calcium oxide content in unaged steel slag to less than 3% within 24 hours in combination with the preparation process of conventional steel slag aggregate, and can realize the rapid preparation of high-quality steel slag aggregate, thereby solving the technical problems of high free calcium oxide in conventional steel slag aggregate, long cycle and low efficiency of existing treatment methods.
[0006] To achieve the above object, according to one aspect of the present invention, a method for rapidly preparing high-quality steel slag aggregate is provided, which adopts a graded carbonization process and specifically comprises the following steps:
[0007] (1) Primary carbonization and reduction: using molten steel slag at 1300°C-1500°C as raw material, industrial waste gas is continuously introduced into the hot stuffy tank for carbonization for 8h-14h during the water spray cooling process, and at the same time, the ferric oxide in the steel slag is reduced to elemental iron and ferrous oxide, thereby obtaining primary carbonized steel slag; the volume proportion of CO2 in the industrial waste gas is 20%-30%, and the volume proportion of CO is 30%-60%;
[0008] (2) Secondary carbonization: The primary carbonized steel slag with a size of less than 10 mm in step (1) is selected as aggregate, placed in a closed container, sprayed with the steel slag aggregate according to a preset spraying amount, the pressure in the closed container is maintained at 0.3-0.5 MPa, and the same industrial waste gas is continuously introduced into the closed container for secondary carbonization, so that the free calcium oxide content in the steel slag aggregate is less than 3%; and high-quality steel slag aggregate after secondary carbonization is obtained by magnetic separation.
[0009] Preferably, in the method for rapidly preparing high-quality steel slag aggregate, industrial waste gas is continuously introduced into the hot stuffy tank in step (1) for carbonization for 10 to 12 hours to obtain first-grade carbonized steel slag.
[0010] Preferably, in the method for rapidly preparing high-quality steel slag aggregate, the volume proportion of CO2 in the industrial waste gas is 20%-25%, and the volume proportion of CO is 35%-50%. The industrial waste gas is continuously introduced into the hot stuffy tank in step (1) for carbonization for 10 hours to obtain primary carbonized steel slag.
[0011] Preferably, in the method for rapidly preparing high-quality steel slag aggregate, the preset spraying amount in step (2) is 5% to 15% of the mass of the steel slag aggregate, and the secondary carbonization time is 1 hour to 12 hours.
[0012] Preferably, in the method for rapidly preparing high-quality steel slag aggregate, the preset spraying amount is 10% to 15% of the mass of the steel slag aggregate, the pressure in the closed container in step (2) is maintained stable, and the same industrial waste gas is continuously introduced for carbonization for 6 hours to 9 hours.
[0013] Preferably, the method for rapidly preparing high-quality steel slag aggregate comprises maintaining the pressure in the closed container in step (2) stable and continuously introducing industrial waste gas for carbonization for 6 hours.
[0014] Preferably, the method for rapidly preparing high-quality steel slag aggregate further comprises tertiary carbonization and / or quaternary carbonization, wherein the tertiary carbonization is to spray the steel slag aggregate after the secondary carbonization according to a preset spraying amount, maintain the pressure in the closed container at 0.3-0.5 MPa, and continuously introduce the same industrial waste gas for carbonization for 3-6 hours to obtain the tertiary carbonized steel slag aggregate;
[0015] The four-stage carbonization is to spray the three-stage carbonized steel slag aggregate according to a preset spraying amount, maintain the pressure in the closed container at 0.3-0.5 MPa, and continuously introduce the same industrial waste gas for carbonization for 1-2 hours.
[0016] Preferably, in the method for rapidly preparing high-quality steel slag aggregate, the tertiary carbonization and / or quaternary carbonization is sprayed with an acidic solution having a pH of 2 to 4, the preset spraying amount is 10% of the mass of the steel slag aggregate, the pressure in the closed container is maintained at 0.3 MPa, and industrial waste gas is continuously introduced for carbonization for 3 hours during the tertiary carbonization; and industrial waste gas is continuously introduced for carbonization for 1 hour during the quaternary carbonization.
[0017] According to another aspect of the present invention, there is also provided a high-quality steel slag aggregate, which is prepared according to the method of the present invention, has a free calcium oxide content of less than 3.0%, and an apparent relative density of 3.2 to 3.3.
[0018] Preferably, the high-quality steel slag aggregate has a free calcium oxide content of 1.2% to 1.7% and an iron content of ≤1.1%.
[0019] According to another aspect of the present invention, there is also provided a use of the steel slag aggregate as described in the present invention in preparing asphalt concrete.
[0020] In general, compared with the prior art, the above technical solution conceived by the present invention can achieve the following beneficial effects by using molten steel slag as raw material and adopting a graded carbonization process:
[0021] The method for rapidly preparing high-quality steel slag aggregate provided by the present invention uses steel slag in a molten state at 1300°C-1500°C as raw material, uses industrial waste gas with a volume ratio of 20%-30% of CO2 and a volume ratio of 30%-60% of CO for graded carbonization, and uses CO in the industrial waste gas to reduce ferric oxide in the steel slag to elemental iron and ferroferric oxide during high-temperature primary carbonization; then uses the primary carbonized steel slag as aggregate, introduces the same industrial waste gas for secondary carbonization to make the free calcium oxide content in the steel slag less than 3%, and obtains low-density high-quality steel slag aggregate by magnetic separation. The method can be combined with the conventional steel slag preparation process to reduce the free calcium oxide content in the unaged steel slag to less than 3% within 24 hours, thereby realizing the rapid and direct preparation of high-quality steel slag aggregate for the preparation of asphalt concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the AC-10 asphalt mixture gradation curve;
[0023] Figure 2 It is the morphological characteristics of steel slag before and after carbonization under an optical microscope;
[0024] Figure 3 It is a comparison of the mechanical properties of steel slag before and after carbonization. DETAILED DESCRIPTION
[0025] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0026] Steel slag is a by-product of the steelmaking process. It is mainly produced by the reaction of molten iron with slag-forming materials such as lime when steelmaking is carried out under high temperature conditions. When the slag accumulates to a certain amount, it needs to be discharged from the furnace. The discharged slag is cooled to form solid conventional steel slag. The steel slag raw materials are crushed, graded and screened to obtain steel slag aggregates of different particle sizes. Among them, steel slag aggregates generally refer to steel slag with a particle size between 0.075mm and 10mm. 4.75mm is used as the boundary particle size between coarse and fine steel slag aggregates. The specific particle size of fine steel slag aggregates is 0.075mm-2.36mm. Coarse steel slag aggregates usually include two grades, namely coarse steel slag aggregates with a particle size of 2.36mm-4.75mm and coarse steel slag aggregates with a particle size of 4.75mm-10mm. The particle size of fine steel slag powder is generally micron level. The existing carbonization process mainly carbonizes steel slag fine powder. Although it can reduce its free calcium oxide content to below 3%, it is difficult to achieve such a reduction when directly applied to steel slag aggregate. This is mainly because steel slag aggregate with a particle size of more than 1 mm has a small specific surface area and is difficult to directly adsorb and carbonize CO2.
[0027] In view of the fact that existing steel slag aggregates are difficult to carbonize quickly, the present invention explores a carbonization process suitable for steel slag aggregates to achieve the purpose of quickly reducing the free calcium oxide in the steel slag aggregates. The inventor combined the preparation process of conventional steel slag and conducted a large number of experimental explorations. The results showed that using high-temperature molten steel slag as raw material and adopting a graded carbonization process can quickly reduce the free calcium oxide content in the steel slag aggregate to meet the technical requirements. The graded carbonization process includes primary carbonization and reduction, and secondary carbonization, wherein the primary carbonization and reduction uses 1300℃-1500℃ molten unaged steel slag as raw material, pours the raw material into a hot stuffy tank, and continuously introduces industrial waste gas during the water spray cooling process for carbonization for 8h~14h. At the same time, the ferric oxide in the steel slag is reduced to elemental iron and ferroferric oxide by CO in the industrial waste gas to obtain primary carbonized steel slag. The volume proportion of CO2 in the industrial waste gas is 20%-30%, and the volume proportion of CO is 20%-30%. The carbonization rate is 30% to 60%; the secondary carbonization is to select the primary carbonized steel slag below 10mm as aggregate, spray the primary carbonized steel slag according to the preset spraying amount, place the sprayed primary carbonized steel slag aggregate in a closed container, maintain the pressure in the closed container at 0.3 to 0.5Mpa, and continuously introduce the same industrial waste gas for carbonization for 1h to 12h, and the preset spraying amount accounts for 5% to 15% of the mass of the steel slag aggregate; magnetic separation obtains high-quality steel slag aggregate after secondary carbonization, i.e., secondary carbonized steel slag aggregate.
[0028] According to this method, a high-quality steel slag aggregate with a free calcium oxide content of less than 3% can be prepared within 24 hours, which meets the technical requirements of the transportation industry standard "Steel Slag for Asphalt Mixture" JT / T 1086-2016) and has a lower density and can be used to prepare asphalt concrete.
[0029] Based on this, the present invention provides a method for quickly preparing high-quality steel slag aggregate, which comprises the following steps:
[0030] (1) Primary carbonization and reduction: using molten unaged steel slag at 1300°C-1500°C as raw material, the raw material is poured into a hot stuffy tank, and industrial waste gas is continuously introduced into the hot stuffy tank during water cooling for carbonization for 8h-14h, while the ferric oxide in the steel slag is reduced to elemental iron and ferrous oxide by CO in the industrial waste gas, thereby obtaining primary carbonized steel slag; the volume proportion of CO2 in the industrial waste gas is 20%-30%, and the volume proportion of CO is 30%-60%;
[0031] (2) Secondary carbonization: The primary carbonized steel slag obtained in step (1) is screened, and the primary carbonized steel slag with a size of less than 10 mm is selected as aggregate. The primary carbonized steel slag is sprayed according to a preset spraying amount to precipitate free calcium oxide in the steel slag aggregate. The steel slag aggregate after water spraying is placed in a sealed container, and the pressure in the sealed container is maintained at 0.3-0.5 MPa. The same industrial waste gas is continuously introduced into the sealed container for secondary carbonization, so that the free calcium oxide content in the steel slag aggregate is less than 3%; magnetic separation is performed to obtain high-quality steel slag aggregate after secondary carbonization. The primary carbonized steel slag with a size of more than 10 mm is washed with water and then transferred to a double-roll crusher for re-crushing.
[0032] In step (1), under high temperature conditions of 900°C to 1500°C, CO in industrial waste gas reacts with non-magnetic Fe2O3 in molten steel slag to generate elemental Fe and CO2. Under specific conditions above 600°C, CO in industrial waste gas reacts with non-magnetic Fe2O3 in molten steel slag to generate magnetic Fe3O4 and CO2. Free calcium oxide in molten steel slag reacts with water vapor to generate calcium hydroxide. When the temperature drops below 600°C, CO2 in industrial waste gas reacts with the precipitated Ca 2+ The reaction generates stable CaCO3, which initially carbonizes the molten slag raw material. The free calcium oxide and magnesium oxide in the slag react with water to cause the aggregate to expand by 1-2 times, accelerating the cracking of large pieces of slag. Finally, the large aggregate becomes small aggregate, exposing more active ingredients that can continue to react with water, which is beneficial to improving the carbonization effect of the exhaust gas.
[0033] In the present invention, the CO2 produced by the reduction reaction in the primary carbonization stage supplements the CO2 consumed by the carbonization reaction in the hot stuffy tank, which can promote the continuous progress of the carbonization reaction. At the same time, the carbonization reaction consumes the CO2 produced by the reduction reaction, which in turn promotes the reduction reaction to form more elemental iron and magnetic Fe3O4. The two promote each other, and can form more elemental iron and magnetic Fe3O4 while improving the stability of the slag, thereby improving the magnetism of the solid slag, which is beneficial to the magnetic separation of iron and magnetic Fe3O4 in the slag, thereby reducing the density of the slag, and also avoiding the waste of metallic iron oxide resources in the slag.
[0034] Preferably, during the primary carbonization, industrial waste gas is continuously introduced into the hot stuffy tank in step (1) for carbonization for 10 to 12 hours to obtain primary carbonized steel slag.
[0035] In some embodiments, the volume proportion of CO2 in the industrial waste gas is 20%-25%, and the volume proportion of CO is 35%-50%. The industrial waste gas is continuously introduced into the hot stuffy tank in step (1) for carbonization for 10 hours to obtain primary carbonized steel slag.
[0036] Preferably, the preset spraying amount is 5% to 15% of the mass of the primary carbonized steel slag aggregate. The same industrial waste gas is continuously introduced into the closed container in step (2) for carbonization for 1 hour to 12 hours, so that the free calcium oxide content in the steel slag aggregate is less than 3%, and high-quality steel slag aggregate is obtained after secondary carbonization by magnetic separation.
[0037] In some embodiments, pure water is used for spraying during secondary carbonization, and the preset spraying amount is 10-15% of the mass of the primary carbonized slag aggregate. The pressure in the closed container in step (2) is maintained at 0.3-0.5 MPa, and industrial waste gas is continuously introduced for carbonization for 3h-9h, preferably for 6h-9h, and more preferably for 6h.
[0038] In some embodiments, pure water is used for spraying during secondary carbonization, and the preset spraying amount is 10% of the mass of the primary carbonized slag. The pressure in the sealed container is maintained at 0.3 MPa, and industrial waste gas is continuously introduced for carbonization for 6 hours.
[0039] Furthermore, the method further includes a tertiary carbonization and / or a quaternary carbonization, wherein the tertiary carbonization is to spray the steel slag aggregate after the secondary carbonization according to a preset spraying amount, maintain the pressure in the closed container at 0.3-0.5 MPa, and continuously introduce the same industrial waste gas for carbonization for 3-6 hours to obtain the tertiary carbonized steel slag aggregate;
[0040] The four-stage carbonization is to spray the three-stage carbonized steel slag aggregate according to a preset spraying amount, maintain the pressure in the closed container at 0.3-0.5 MPa, and continuously introduce the same industrial waste gas for carbonization for 1-2 hours.
[0041] In some embodiments, the tertiary carbonization or the quaternary carbonization is carried out by spraying with pure water or an acidic solution with a pH value of 2 to 4, and the preset spraying amount is 10% of the mass of the slag aggregate. Preferably, during the tertiary carbonization, the pressure in the closed container is maintained at 0.3 MPa, and industrial waste gas is continuously introduced for carbonization for 3 hours; preferably, during the quaternary carbonization, the pressure in the closed container is maintained at 0.3 MPa, and industrial waste gas is continuously introduced for carbonization for 1 hour; more preferably, an acidic solution with a pH value of 2 to 4 is used for spraying.
[0042] In addition, the present invention also provides a high-quality steel slag aggregate, which is prepared according to the method of the present invention, has a free calcium oxide content of less than 3.0%, and an apparent relative density of 3.2 to 3.3.
[0043] Preferably, the steel slag aggregate has a free calcium oxide content of 1.2-1.7% and an iron content of ≤1.1%.
[0044] According to another aspect of the present invention, there is also provided a use of the steel slag aggregate as described in the present invention in preparing asphalt concrete.
[0045] The following are examples
[0046] Example 1 Graded Carbonization of Steel Slag Aggregate
[0047] In this embodiment, hot molten slag from a steel plant is used as a raw material to prepare high-quality steel slag aggregate, wherein the chemical composition of the steel slag is shown in the following table.
[0048] Table 1 Chemical composition of steel slag raw materials
[0049] composition MgO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> <![CDATA[P2O5]]> CaO MnO <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> other Percentage content (wt%) 5.9 4.3 13.2 1.8 38.7 3.9 25.3 0.7 6.2
[0050] The CaO in the table includes inactive calcium oxide and active free calcium oxide (f-CaO), among which f-CaO is the key factor affecting the stability of steel slag. In terms of percentage, the f-CaO content in unaged steel slag raw materials is generally 5% to 8%. After testing, the f-CaO content in the steel slag raw materials is 5.36%.
[0051] According to China Science Daily and Nature: Chemical Engineering, a subsidiary of the top international journal Nature, the main components of industrial waste gas are shown in Table 2.
[0052] Table 2 Composition of industrial waste gas from steel mills
[0053] Gas source CO(%) <![CDATA[CO2(%)]]> <![CDATA[N2(%)]]> <![CDATA[H2(%)]]> <![CDATA[CH4(%)]]> Blast furnace gas 21-25 20-22 50-59 1-3 - Converter gas 39-48 20-22 20-30 1 - Coke oven gas 7-9 1-3 2-5 50-60 21-26
[0054] The industrial waste gas used in this embodiment comes from steelmaking converter gas, in which CO2 accounts for 20%-22% by volume and CO accounts for 39%-48% by volume. Molten steel slag is used as raw material for primary carbonization and reduction treatment, and the effects of industrial waste gas on the carbonization effect of steel slag under different carbonization conditions are compared, as follows:
[0055] (1) Effect of different carbonization times on the primary carbonization effect of molten steel slag
[0056] Primary carbonization and reduction: Pour molten steel slag raw materials at 1300℃-1500℃ into a hot stuffy tank, continuously sprinkle water on the surface of the molten steel slag raw materials, and introduce industrial waste gas into it for primary carbonization and reduction. The effects of different carbonization conditions on the carbonization effect of steel slag are compared, as follows.
[0057] Table 3 Effect of different carbonization time on f-CaO content of steel slag coarse aggregate
[0058]
[0059]
[0060] It can be seen from the results of Table 3 that with the extension of the primary carbonization time, the f-CaO content of the steel slag shows a trend of first decreasing and then stabilizing. After 8 hours of primary carbonization, the f-CaO content of the steel slag decreased from 5.36% to 3.61%, a decrease of 32.65%, but with the continued extension of the carbonization time, the f-CaO content of the steel slag did not change significantly. However, as the steel slag is subjected to the primary carbonization process, the temperature in the hot stuffy tank decreases over time, and the steel slag changes from a molten state to a solid state, which easily forms large pieces of solid steel slag. In order to fully crack the large pieces of solid steel slag (to avoid being difficult to break in the later stage), the carbonization time is usually extended by several hours, that is, the preferred primary carbonization time is screened out to be 10-12 hours, and the more preferred primary carbonization time is 10 hours.
[0061] From the results in the table above, it can be seen that even if the primary carbonization time is extended, the f-CaO content of steel slag aggregate is basically maintained at 3.5-3.6%, which is difficult to reduce further, and does not meet the technical requirements of the transportation industry standard "Steel Slag for Asphalt Mixture" JT / T 1086-2016): steel slag f-CaO ≤ 3%. It can be seen that it is difficult to make the f-CaO content of steel slag aggregate meet the relevant technical requirements by carbonizing it once.
[0062] Although the free calcium oxide content of steel slag after primary carbonization is higher than 3%, the heat generated in the steel slag production process can be fully utilized during the primary carbonization process (the temperature of molten steel slag can reach 1300-1500°C), and the ferric oxide in the steel slag can undergo a reduction reaction with CO under high temperature conditions above 600°C, that is, during the primary carbonization process, the non-magnetic ferric oxide in the steel slag is reduced to magnetic iron and ferroferric oxide by CO in the industrial waste gas. The iron and ferroferric oxide are screened out by magnetic separation, which can not only reduce the density of the steel slag aggregate after carbonization, but also help reduce the transportation cost of the steel slag, and at the same time reduce the amount of asphalt required for the preparation of asphalt concrete, but also avoid the waste of iron resources in the steel slag, and also reduce the emission of CO and CO2 in the industrial waste gas.
[0063] (2) Effect of different pressures on secondary carbonization effect
[0064] Furthermore, based on the primary carbonized steel slag aggregate obtained after 14h of primary carbonization, the effects of different pressures on the secondary carbonization effect of steel slag aggregate were studied as follows:
[0065] The primary carbonized steel slag aggregate with a diameter of less than 10 mm was selected, sprayed according to the preset spraying amount, and placed in a closed container and introduced with the same industrial waste gas for secondary carbonization. The industrial waste gas was introduced to maintain the pressure in the closed container at a set value (0.1Mpa, 0.3Mpa, or 0.5Mpa). The effect of different carbonization conditions on the f-CaO content in the steel slag aggregate was measured. The results are as follows:
[0066] Table 4 Changes of f-CaO content in steel slag aggregates under different carbonization conditions
[0067]
[0068]
[0069] It can be seen from the measurement results in Table 4 that, under the condition of the same preset spraying amount, the carbonization effect of steel slag aggregate is better under the pressure of 0.3-0.5 MPa, and graded carbonization is preferably carried out under a pressure of 0.3 MPa.
[0070] (2) Effect of spraying amount and carbonization time on graded carbonization effect of steel slag aggregate
[0071] A 150mm ground screen was used to screen the primary carbonized steel slag, and the steel slag particles with a particle size of less than 150mm were qualified materials. Steel slag aggregates with a size of less than 10mm (0.075-10mm) were selected from the qualified materials (the steel slag aggregates with a size of more than 10mm were washed with water and conveyed to a roller crusher by a conveyor belt for re-crushing to select steel slag aggregates with a size of less than 10mm). Under the condition of a carbonization pressure of 0.3Mpa, the selected steel slag aggregates with a size of less than 10mm were subjected to graded carbonization treatment, and the effects of pure water spraying amount and carbonization time on the carbonization effect of steel slag were studied to determine the optimal carbonization process, as follows:
[0072] Table 5 Effect of spraying amount and carbonization time on secondary carbonization effect of steel slag aggregate
[0073]
[0074]
[0075]
[0076] It can be seen from the measurement results in Table 5 that when the preset spraying amount is 10% to 15% of the mass of the steel slag aggregate and the secondary carbonization time is ≥1h, or when the preset spraying amount is 5% of the mass of the steel slag aggregate and the secondary carbonization time is ≥3h, the free calcium oxide content of the steel slag aggregate after secondary carbonization is <3.0%, which meets the technical requirements of the transportation industry standard "Steel Slag for Asphalt Mixture" JT / T 1086-2016).
[0077] Under the same pure water spraying conditions, as the carbonization time increases, the free calcium oxide content of the steel slag shows a trend of first decreasing and then stabilizing. Increasing the spraying amount is beneficial to improving the carbonization effect. Considering comprehensively, the preferred secondary carbonization conditions are as follows: the preset spraying amount is 10%, the industrial waste gas is introduced to make the pressure in the closed container reach 0.3Mpa, and this pressure is maintained for continuous ventilation and carbonization for 6 to 9 hours. According to the carbonization conditions, the free calcium oxide content of the steel slag can be reduced to about 2.10% by secondary carbonization, which is more than 41% lower than that of the primary carbonized steel slag; the preferred secondary carbonization time is 6 hours.
[0078] After the secondary carbonization, the steel slag is subjected to magnetic separation by a magnetic separation device, which mainly separates metals such as iron, and obtains elemental iron and steel slag aggregates with a low density below 10 mm. The apparent relative density of the steel slag aggregate after magnetic separation of the secondary carbonized steel slag is about 3.3, and the apparent density of the untreated steel slag aggregate is 3.5. The carbonization treatment of steel slag raw materials by this method can not only significantly shorten the time required to carbonize the steel slag aggregate to a free calcium oxide content of ≤3%, realize rapid and efficient carbonization treatment, but also reduce the density of the steel slag after carbonization.
[0079] Furthermore, the third-level carbonization was carried out on the basis of the second-level carbonized steel slag aggregate obtained by completing the second-level carbonization at the preset spraying amount of 5%, 10% and 15% and the second-level carbonization time of 12h, and the influence of the carbonization conditions of the third-level carbonization on the carbonization effect of the steel slag aggregate was studied, as follows:
[0080] Screen the secondary carbonized steel slag aggregates below 10mm (crush the steel slag aggregates above 10mm, and the needle-like content of the crushed steel slag aggregates is required to be no higher than 15%). Place the selected secondary carbonized steel slag aggregates below 10mm in a closed container, and continuously introduce the same industrial waste gas to compare the effects of different pure water spraying amounts and carbonization time on the tertiary carbonization effect of the steel slag aggregates, as follows:
[0081] Table 6 Effect of spraying amount and carbonization time on the three-stage carbonization effect of steel slag aggregate
[0082]
[0083]
[0084] The secondary carbonized steel slag aggregate is evenly sprinkled with water according to a preset spraying amount to keep the surface of the steel slag moist, and the secondary carbonized steel slag aggregate after watering is placed in a closed container, and the same industrial waste gas is continuously introduced for carbonization. It can be seen from the measurement results in Table 6 that the preset spraying amount of pure water is 10% to 15% of the mass of the secondary carbonized steel slag aggregate, and carbonization for more than 3 hours can reduce the free calcium oxide content in the steel slag aggregate to less than 2%. The preferred tertiary carbonization time is 3 to 6 hours, and more preferably the preset spraying amount of the tertiary carbonization is 10%, and the tertiary carbonization time is 3 hours.
[0085] Furthermore, based on the three-stage carbonized steel slag obtained by the three-stage carbonization with the preset spraying amount of 5%, 10% and 15% and the three-stage carbonization time of 12h, the four-stage carbonization was carried out to study the influence of the carbonization conditions of the four-stage carbonization on the carbonization effect of the steel slag aggregate, as follows:
[0086] The three-level carbonized steel slag aggregate is magnetically separated, and the steel slag aggregate after magnetic separation is crushed again. The needle-like content of the crushed steel slag aggregate is required to be no higher than 15%. The crushed three-level carbonized steel slag aggregate is placed in a closed container, and the same industrial waste gas is continuously introduced. The effects of different spraying amounts and carbonization times on the carbonization effect of the steel slag aggregate are compared as follows:
[0087] Table 7 Effect of spraying amount and carbonization time on the four-stage carbonization effect of steel slag aggregate
[0088]
[0089]
[0090]
[0091] It can be seen from the test results in Table 7 that in the fourth-level carbonization stage, the carbonization effect of steel slag aggregate is not significantly improved with the extension of carbonization time. The preset spraying amount is 10% to 15%, and the carbonization time is 1h, the overall carbonization effect is better, and the carbonization effect of steel slag aggregate is not significantly improved when the carbonization time is further extended. Comprehensively considered, the preferred preset spraying amount for the fourth-level carbonization is 10%, the carbonization time is 1h, the overall carbonization effect is better, and the carbonization cycle is short.
[0092] Example 2 Preparation of high-quality steel slag aggregate
[0093] Using hot slag from the steelmaking process as raw material, converter gas as industrial waste gas for four-stage carbonization treatment to prepare high-quality steel slag aggregate, and using solid waste steel slag cooled by hot stewing as raw material, using pure CO2 for carbonization treatment as a control, the details are as follows:
[0094] Primary carbonization and reduction: Using molten steel slag at 1300℃-1500℃ as raw material, pour the raw material into a hot stuffy tank, continuously sprinkle water on the surface of the raw material, and introduce industrial waste gas (converter gas) produced by converter steelmaking into the hot stuffy tank for carbonization for 10 hours, so that the industrial waste gas and steel slag are fully in contact, so that the free calcium oxide in the steel slag reacts with water vapor, CO2 and CO in the industrial waste gas in a series of reactions, so that the free calcium oxide in the steel slag is carbonized to form calcium carbonate, and the non-magnetic Fe2O3 in the steel slag is reduced to elemental Fe and Fe3O4, so as to obtain primary carbonized steel slag.
[0095] Screening with 150mm floor sieve: The first-grade carbonized steel slag is screened with 150mm floor sieve, and the steel slag particles with a particle size of less than 150mm are qualified materials. The unqualified materials are recycled and the above operation is repeated until the standards are met.
[0096] First-stage vibration screening: First-stage carbide steel slag below 10mm is screened from qualified materials as aggregate. First-stage carbide steel slag aggregate above 10mm is washed with water and transported to the double-roll crusher by conveyor belt for re-crushing, and second-stage vibration screening is carried out to first-stage carbide steel slag aggregate below 10mm.
[0097] Primary watering: Sprinkle water evenly at 10% of the mass of the slag aggregate to keep the surface of the slag moist, so that the free calcium oxide in the slag can continue to precipitate outward, which is beneficial to improving the secondary carbonization effect.
[0098] Secondary carbonization: Place the steel slag aggregate after watering in a closed container, maintain the pressure in the closed container at 0.3Mpa, and continuously introduce the same industrial waste gas for carbonization for 6 hours to further reduce the free calcium oxide content in the steel slag aggregate.
[0099] Primary magnetic separation: The secondary carbide steel slag aggregate is subjected to primary magnetic separation through a magnetic separation device, which mainly separates metals such as iron to obtain elemental iron and secondary carbide steel slag aggregate with a low iron content (iron content ≤ 1.1%) below 10 mm.
[0100] Three-stage carbonization: Use a double-roll crusher to crush the secondary carbonized steel slag aggregate, and the needle-like content of the crushed steel slag aggregate is required to be no higher than 15%. Place the crushed secondary carbonized steel slag aggregate that meets the requirements in a closed container, maintain the pressure in the closed container at 0.3Mpa, and continue to introduce the same industrial waste gas for carbonization for 3 hours to further reduce the free calcium oxide content of the steel slag aggregate, and obtain the three-stage carbonized steel slag aggregate.
[0101] Secondary magnetic separation: The tertiary carbide steel slag aggregate is subjected to secondary magnetic separation through a magnetic separation device to obtain elemental iron and low-density tertiary carbide steel slag aggregate. The apparent relative density of the steel slag aggregate after magnetic separation is 3.2, which is lighter than the untreated 3.5, which is beneficial to reducing the transportation cost of the steel slag aggregate and at the same time can reduce the actual amount of asphalt used.
[0102] Four-stage carbonization: Use a cone crusher to re-crush the three-stage carbonized steel slag aggregate after the secondary magnetic separation. The needle-like content of the crushed steel slag aggregate is required to be no higher than 15%. Place the crushed three-stage steel slag aggregate that meets the requirements in a closed container, maintain the pressure in the closed container at 0.3Mpa, and continue to introduce the same industrial waste gas for carbonization for 1 hour to obtain the four-stage carbonized steel slag aggregate.
[0103] Three-stage magnetic separation: The obtained four-stage carburized steel slag aggregate is passed through a magnetic separation device for three-stage magnetic separation to obtain elemental iron, thereby further reducing the density of the steel slag aggregate.
[0104] Secondary vibration screening: steel slag aggregates below 4.75mm are selected, and steel slag aggregates above 4.75mm are washed with water and then conveyed to the double-roll crusher via a conveyor belt for re-crushing.
[0105] Three-stage vibration screening: The washed and crushed steel slag aggregate is screened to obtain steel slag powder below 0.075mm with excellent stability and outstanding first-level mechanical properties, 0.075mm-2.36mm steel slag fine aggregate (0.075mm-3mm during construction), 2.36mm-4.75mm steel slag coarse aggregate (3mm-5mm during construction) and 4.75mm-10mm steel slag coarse aggregate (5mm-10mm during construction).
[0106] The above-mentioned first-stage vibration screening is a first-stage vibration single-layer vibration, the vibration screen angle is 15°~25°, the double amplitude is 8mm, the vibration frequency is 870Hz and 970Hz, and the screen hole diameter is 10mm or 11mm;
[0107] The above-mentioned two-stage vibration screening is a two-stage vibration single-layer vibration, the vibration screen angle is 15°~25°, the double amplitude is 8mm, the vibration frequency is 870Hz and 970Hz, and the screen hole diameter is 4.75mm or 6mm;
[0108] The above-mentioned three-stage vibration screening is a three-stage single-layer vibration, the vibration screen angle is 15°~25°, the double amplitude is 8mm, the vibration frequency is 870Hz and 970Hz, and the screen hole diameters are 4.75mm, 2.36mm and 0.075mm.
[0109] The above conveyor belts are connected by belt conveyors, and the belt speed range of the belt conveyor is set to 0.8-1.2m / s. At the same time, considering the impact of aggregate particle size on transmission, the specific transmission rate recommendations are as follows: the rate of the first-stage vibration screening-second-stage carbonization tank is 0.8m / s, the rate of the first-stage magnetic separation-roller crusher is 0.8m / s, the rate of the roller crusher-third-stage carbonization tank is 1.0m / s, the rate of the second-stage magnetic separation-cone crusher is 1.0m / s, the rate of the cone crusher-fourth-stage carbonization tank is 1.0m / s, the rate of the third-stage magnetic separation-second-stage vibration screening is 0.8m / s, and the rate of the third-stage vibration screen-discharging is 1.2m / s.
[0110] The steel slag aggregates of a production line with an hourly output of 100 tons were tested to measure the performance indicators of the steel slag aggregates prepared in this embodiment and the aggregates prepared by the original process. According to the requirements of T304-2005, the performance indicators of the steel slag aggregates prepared in this embodiment and the aggregates prepared by the original process were measured respectively. Figure 1 The asphalt mixture gradation of AC-10 shown in the figure was used to prepare the corresponding steel slag mixture before and after improvement for expansion test, as follows:
[0111] according to Figure 1 The AC-10 asphalt mixture gradation curve shown in the figure is that the steel slag of each grade before and after improvement is prepared into steel slag mixture, and the steel slag mixture is placed in a constant temperature water tank at 80℃ for 7 days. According to the expansion rate formula: The daily expansion rate of steel slag aggregate before and after the improvement was calculated, and the average value of three tests after 7 days of insulation was taken as the final result. According to the proportion of coarse aggregate in on-site construction, it is generally more than 60%, so the on-site record will write the expansion rate into the coarse aggregate test table, and the results are shown in Table 8.
[0112] In the above formula, C1 is the expansion rate of slag aggregate, D i is the aggregate expansion rate reading on the i-th day, and D0 is the initial expansion rate reading of the aggregate placed in the constant temperature water tank.
[0113] In addition, according to the requirements of T304-2005, the optimal moisture content of the carbonized steel slag mixture was obtained through experiments. The results are shown in the following table.
[0114] Table 8 Technical test results of steel slag coarse aggregate before and after improvement
[0115]
[0116]
[0117] Table 9 Test results of technical indicators of steel slag fine aggregate before and after improvement
[0118]
[0119] Taking the process before improvement as the control group, the original process (control group) in Tables 8 and 9 is to use the hot molten slag in the steelmaking process as the raw material for four-stage carbonization by treating it with a hot stewing method and cooling the obtained metallurgical slag solid waste (steel slag), wherein the steel slag particles are sprayed with water to moisten them, sent into the carbonization chamber, the chamber door is closed, and pure CO2 gas is introduced so that the CO2 partial pressure reaches 0.2Mpa (refer to the carbonization conditions in Example 2 in CN110642545 A), and the carbonization time for each stage is the same as that in the above Example 2.
[0120] It can be seen from the measurement results in Tables 8 and 9 that the performance indicators of the steel slag aggregate prepared by this method meet the technical requirements of the transportation industry standard "Steel Slag for Asphalt Mixture" JT / T 1086-2016), and can be used as aggregate for preparing asphalt mixture. Compared with the steel slag aggregate prepared by this method using the original process, its free calcium oxide content is significantly reduced, and its water expansion rate is as low as 0.3%. The steel slag aggregate has better stability and better quality.
[0121] Example 3 Optimization of graded carbonization of steel slag aggregate
[0122] In this example, an acidic industrial waste liquid is added to pure water to prepare an acidic solution with a pH of 2-4 to replace the pure water in Example 2, and the solution is sprayed at a preset spraying amount of 10% of the mass of the slag aggregate. The carbonization treatment is carried out using converter gas to explore the effect of graded carbonization of the slag aggregate, as follows:
[0123] Table 10 Effect of acidic solution on graded carbonization of steel slag aggregate
[0124]
[0125]
[0126] It can be seen from the test results in Table 10 that, compared with spraying pure water, spraying acidic solution on steel slag aggregate and using the same industrial waste gas for graded carbonization treatment has a better effect, especially after the third and fourth stage carbonization are treated with acidic solution spraying, the free calcium oxide content is lower, and the stability of the obtained steel slag aggregate is better.
[0127] Example 4 Performance changes of steel slag before and after carbonization
[0128] (1) Morphological changes of steel slag before and after carbonization
[0129] According to the construction requirements, fresh uncarbonized steel slag fine aggregate (particle size 0.075-3mm) and coarse aggregate (3-5mm), uncarbonized steel slag coarse aggregate (5-10mm) placed outdoors for one month, and steel slag aggregate after secondary carbonization treatment in Example 2 were selected as observation objects, and an optical microscope was used to observe whether there was any change on the surface of the steel slag aggregate before and after carbonization, as follows:
[0130] The steel slag aggregate was washed with tap water and then placed in a 60°C oven for 3 h to ensure that the steel slag aggregate was dry. The dried steel slag aggregate was placed under an optical microscope to observe the surface morphology of each group of steel slag aggregate. The results are as follows: Figure 2 shown.
[0131] Figure 2 (a) is uncarbonized steel slag fine aggregate (particle size 0.075-3mm), (b) is steel slag fine aggregate (particle size 0.075-3mm) after secondary carbonization treatment in Example 2, (c) is uncarbonized steel slag coarse aggregate (particle size 3-5mm), (d) is steel slag coarse aggregate (particle size 3-5mm) after secondary carbonization treatment in Example 2, (e) is uncarbonized steel slag coarse aggregate (particle size 5-10mm) placed outdoors for 1 month, and (f) is steel slag coarse aggregate (particle size 5-10mm) after secondary carbonization treatment in Example 2.
[0132] Depend on Figure 2 From the observed surface morphology of steel slag aggregate, it can be seen that white crystals (CaCO3) gradually appear on the surface of carbonized steel slag, and the surface color changes from brown-green to white. During the carbonization process, the steel slag reacts chemically with CO2 in the industrial waste gas to generate CaCO3, which changes the morphological characteristics of the steel slag surface. The surface of the uncarbonized steel slag aggregate is relatively smooth, and the overall color is brown-green.
[0133] (2) Changes in mechanical properties of steel slag before and after carbonization
[0134] Compounding was performed according to the grading of AC-10, and then 3000g of the mixture with a diameter of 2.36mm or larger was screened out using a 2.36mm sieve for testing. The improved crushing value test was used to test the mechanical properties of steel slag aggregate before and after carbonization, as follows:
[0135] According to the requirements of the "Highway Engineering Aggregate Test Code" JTG E42-2005, four groups of 3000g of steel slag (compounded according to the grading of AC-10) were weighed and placed in the mold, recorded as m0. Subsequently, the test was carried out with loads of 200kN, 400kN, 600kN and 800kN respectively, and the crushed steel slag was passed through a 2.36mm sieve, and the mass of the sieved steel slag was weighed and recorded as m1. Each group was repeated 3 times, and according to the crushing value formula: Calculate the crushing value of each group, the result is as follows Figure 3 As shown. Figure 3 It can be seen that compared with the uncarbonized steel slag, the crushing value of the carbonized steel slag prepared according to the present method is reduced and its mechanical properties are improved.
[0136] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for rapidly preparing high-quality steel slag aggregate, characterized in that: The graded carbonization process is adopted, which specifically includes the following steps: (1) Primary carbonization and reduction: using molten steel slag at 1300°C-1500°C as raw material, industrial waste gas is continuously introduced into the hot stuffy tank for carbonization for 8h-14h during the water spray cooling process, and at the same time, the ferric oxide in the steel slag is reduced to elemental iron and ferrous oxide, thereby obtaining primary carbonized steel slag; the volume proportion of CO2 in the industrial waste gas is 20%-30%, and the volume proportion of CO is 30%-60%; (2) Secondary carbonization: The primary carbonized steel slag with a size of less than 10 mm in step (1) is selected as aggregate, placed in a closed container, sprayed with the steel slag aggregate according to a preset spraying amount, the pressure in the closed container is maintained at 0.3-0.5 MPa, and the same industrial waste gas is continuously introduced into the closed container for secondary carbonization, so that the free calcium oxide content in the steel slag aggregate is less than 3%; and high-quality steel slag aggregate after secondary carbonization is obtained by magnetic separation.
2. The method for rapidly preparing high-quality steel slag aggregate according to claim 1, characterized in that: Industrial waste gas is continuously introduced into the hot stuffy tank in step (1) for carbonization for 10 to 12 hours to obtain first-grade carbonized steel slag.
3. The method for rapidly preparing high-quality steel slag aggregate according to claim 2, characterized in that: The volume proportion of CO2 in the industrial waste gas is 20%-25%, and the volume proportion of CO is 35%-50%. The industrial waste gas is continuously introduced into the hot stuffy tank in step (1) for carbonization for 10 hours to obtain primary carbonized steel slag.
4. The method for rapidly preparing high-quality steel slag aggregate according to claim 3, characterized in that: The preset spraying amount in step (2) is 5% to 15% of the mass of the steel slag aggregate, and the secondary carbonization time is 1h to 12h.
5. The method for rapidly preparing high-quality steel slag aggregate according to claim 4, characterized in that: The preset spraying amount is 10% to 15% of the mass of the steel slag aggregate. The pressure in the closed container in step (2) is maintained stable, and the same industrial waste gas is continuously introduced for carbonization for 6 hours to 9 hours.
6. The method for rapidly preparing high-quality steel slag aggregate according to any one of claims 1 to 5, characterized in that: It also includes three-stage carbonization and / or four-stage carbonization, wherein the three-stage carbonization is to spray the steel slag aggregate after the second-stage carbonization according to a preset spraying amount, maintain the pressure in the closed container at 0.3-0.5Mpa, and continuously introduce the same industrial waste gas for carbonization for 3-6 hours to obtain the three-stage carbonized steel slag aggregate; The four-stage carbonization is to spray the three-stage carbonized steel slag aggregate according to a preset spraying amount, maintain the pressure in the closed container at 0.3-0.5 MPa, and continuously introduce the same industrial waste gas for carbonization for 1-2 hours.
7. The method for rapidly preparing high-quality steel slag aggregate according to claim 6, characterized in that: The tertiary carbonization and / or quaternary carbonization is sprayed with an acidic solution with a pH of 2 to 4, the preset spraying amount is 10% of the mass of the slag aggregate, the pressure in the closed container is maintained at 0.3 MPa, and industrial waste gas is continuously introduced for carbonization for 3 hours during the tertiary carbonization; and industrial waste gas is continuously introduced for carbonization for 1 hour during the quaternary carbonization.
8. A high-quality steel slag aggregate, characterized in that: The invention is prepared according to the method as claimed in any one of claims 1 to 7, wherein the free calcium oxide content is less than 3.0% and the apparent relative density is 3.2 to 3.
3.
9. The high-quality steel slag aggregate according to claim 8, characterized in that: The free calcium oxide content in the steel slag aggregate is 1.2% to 1.7%, and the iron content is ≤1.1%.
10. Use of the steel slag aggregate as claimed in claim 8 or 9 in preparing asphalt concrete.
Citation Information
Patent Citations
Steel slag recovery method
CN110396563A
Carbon capture steel slag-based hot flue gas curing concrete as well as preparation method and application thereof
CN116854418A
Method for carbonating and sealing carbon in steel slag in steelmaking process
CN118910341A
Method for treating steelmaking slag
JP2011006300A
Steelmaking slag and manufacturing method of the same
JP2012087002A
Cited By
Preparation method of carbon sequestration steel slag aggregate for asphalt pavement
CN121426448A